The relationship between maternal education and mortality among women giving birth in health care institutions: Analysis of the cross sectional WHO Global Survey on Maternal and Perinatal Health - Karlsen, Saffron; Say, Lale; Souza, João-Paulo; Hogue, Carol J; Calles, Dinorah L; Gülmezoglu, A Metin; Raine, Rosalind (BMC public health, 2011)
Background Approximately one-third of a million women die each year from pregnancy-related conditions. Three-quarters of these deaths are considered avoidable. Millennium Development Goal five calls for a reduction in maternal mortality and the establishment of universal access to high quality reproductive health care. There is evidence of a relationship between lower levels of maternal education and higher maternal mortality. This study examines the relationship between maternal education and maternal mortality among women giving birth in health care institutions and investigates the association of maternal age, marital status, parity, institutional capacity and state-level investment in health care with these relationships. Methods Cross-sectional information was collected on 287,035 inpatients giving birth in 373 health care institutions in 24 countries in Africa, Asia and Latin America, between 2004-2005 (in Africa and Latin America) and 2007-2008 (in Asia) as part of the WHO Global Survey on Maternal and Perinatal Health. Analyses investigated associations between indicators measured at the individual, institutional and country level and maternal mortality during the intrapartum period: from admission to, until discharge from, the institution where women gave birth. There were 363 maternal deaths. Results In the adjusted models, women with no education had 2.7 times and those with between one and six years of education had twice the risk of maternal mortality of women with more than 12 years of education. Institutional capacity was not associated with maternal mortality in the adjusted model. Those not married or cohabiting had almost twice the risk of death of those who were. There was a significantly higher risk of death among those aged over 35 (compared with those aged between 20 and 25 years), those with higher numbers of previous births and lower levels of state investment in health care. There were also additional effects relating to country of residence which were not explained in the model. Conclusions Lower levels of maternal education were associated with higher maternal mortality even amongst women able to access facilities providing intrapartum care. More attention should be given to the wider social determinants of health when devising strategies to reduce maternal mortality and to achieve the increasingly elusive MDG for maternal mortality.